Implementasi Protokol LEACH pada Wireless Sensor Network dengan Perangkat berbasis nRF24L01 - Wahyu Berlianto; Agung Setia Budi; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Low Energy Adaptive Clustering Hierarchy is a protocol based on dynamic cluster tree topology. This protocol can rotate the role of the cluster head periodically, which aims to evenly distribute the load between nodes, thereby increasing the lifetime of the wireless sensor network. Several studies have been conducted on the LEACH, but these studies only implemented the LEACH protocol using network simulation. In this study, the authors implement the LEACH on a real Arduino-based system and nRF24L01 as a data transmission module. This protocol will be compared with protocols based on static clustering. The node module uses Arduino Pro Mini 3.3V, and the base station uses the Arduino Uno microcontroller. LEACH protocol testing is done by monitoring the data received from all nodes through the base station's serial monitor. The data sent from the node is the average current from each node. the test was carried out for one hour, so that the current value used per hour was obtained. With this value, lifetime predictions can be made with a certain battery size. In this case, the battery size used is 1000mAh. The results of the lifetime testing of the system using the the static clustering protocol only lasted about 40 hours, while the results of the lifetime testing of the system using the LEACH protocol have an average lifetime of about 88 hours and 53 minutes, which is an increase by more than twice the lifetime.